1981
DOI: 10.3354/meps006317
|View full text |Cite
|
Sign up to set email alerts
|

Attached and Free-Floating Bacteria in the Fraser River Estuary, British Columbia, Canada

Abstract: The contribution of free-floating bacteria versus bacteria attached to particulate material to the microbiology of the Fraser River Estuary was assessed. Approximately 60 % of bacterial biomass and heterotrophic activity was associated with suspended particulates in the turbid Fraser River (0 Y&o S). The influence of attached bacteria decreased down the estuary as salinity increased dropping to 15-39 % of total bacterial numbers and 4 % of heterotrophic activity in the Strait of Georgia (26 Ym S). Bacteria, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 25 publications
5
41
0
Order By: Relevance
“…This estuary is similar to the Parker River system, and it seems likely that the factors discussed above are also responsible for the distribution of bacteria found by Peterson. Other published works involving the distribution of bacteria in estuaries (Bell and Albright, 1981;Bent and Goulder, 1981) deal with such fundamentally different systems that a comparison of results is not possible. Palumbo and Ferguson (1978) suggested that the bacteria were behaving as conservative constituents in the Newport River estuary, to explain the upper estuary peak and an inverse relation between bacteria numbers and salinity proceeding out into coastal water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This estuary is similar to the Parker River system, and it seems likely that the factors discussed above are also responsible for the distribution of bacteria found by Peterson. Other published works involving the distribution of bacteria in estuaries (Bell and Albright, 1981;Bent and Goulder, 1981) deal with such fundamentally different systems that a comparison of results is not possible. Palumbo and Ferguson (1978) suggested that the bacteria were behaving as conservative constituents in the Newport River estuary, to explain the upper estuary peak and an inverse relation between bacteria numbers and salinity proceeding out into coastal water.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is a consequence of the fact that most of the bacteria were attached to suspended solids. The Fraser River estuary in British Columbia is also characterized by high turbidity and a large proportion of particulate bacteria (Bell and Albright, 1981). Total counts showed an inverse trend with salinity, although heterotrophic activity of the bacteria was generally highest in the plume water of intermediate salinity.…”
Section: Introductionmentioning
confidence: 97%
“…, Grossart & Simon 1998b, Turley & Stutt 2000. In riverine and estuarine systems, however, they may constitute as much as 90% of total bacterial numbers and production (Bell & Albright 1981, Bent & Goulder 1981, Zimmermann & Kausch 1996, Zimmermann 1997, Crump & Baross 2000. In most environments, even with high amounts of suspended matter, the relative proportion of particleassociated bacteria is lower than that of free-living bacteria (Kirchman 1993, Berger et al 1996, Crump & Baross 1996, Crump et al 1998).…”
Section: Prokaryotesmentioning
confidence: 99%
“…Attached bacteria may thus be a substantial food source which, if passed on directly to metazoans, could link the microbial loop (Azam et al 1983) with the grazing food chain. This direct pathway would likely be more important in waters with high particle load such as estuaries and coastal waters, and during post-algal bloom periods where the quantitative significance of production of attached bacteria can be quite high (Bell & Albright 1981). Attached bacteria may also provide a mechanism of energy flow in oligotrophic waters where the primary production is often dominated by picoplankton too small to be efficiently ingested by metazoa and where bacterial carbon can exceed phytoplankton carbon (Fuhrman et al 1989, Cho & Azam 1990).…”
Section: Introductionmentioning
confidence: 99%